Plan estratégico de marketing para el hotel El Auca del cantón Francisco de Orellana, provincia de Orellana, para el periodo 2017-2021 - Ganchozo Mendoza, Ketty Maricela (2017)
The objective of the present investigation is to make a strategic marketing plan for the El Auca Hotel of the canton Francisco de Orellana for the period 2017-2021, province of Orellana, so as to present a proposal to improve the commercial performance of the business. For the development were used such as: deductive, inductive, analytical, synthetic and statistical. In addition, techniques were also used to collect data such as: Interview with the owner and general manager of the Hotel El Auca, Mr. Telmo Messiah Noboa Cabrera. Surveys applied to 376 external clients of the hotel and 36 employees of the same. In the Results section, once the evaluation of the external factors of the company was carried out, the MEFE External Factors Evaluation matrix was constructed, whose weighted result was 3.05, which means that the hotel is responding in an excellent way opportunities against the threats in the sector. In addition, in this same section, it was indispensable to carry out the evaluation of internal factors of the Hotel El Auca of the canton Francisco de Orellana, through the matrix of Evaluation of Internal Factors MEFI, which gave as a weighted result 2.63 which means that it maintains considerable predominance of strengths over weaknesses. Continuing with the development of the thesis, in this same section, based on the matrices MEFE and MEFI, the SWOT matrix was elaborated. Once the different factors of strengths, opportunities, weaknesses and threats were established, the High Impact Matrix for the Hotel El Auca was established. The following four strategies were identified: 1) Attracting new clients to the Hotel El Auca. 2) Increase the level of customer satisfaction in relation to quality of care. 3) Create customer loyalty. 4) Disseminate the offer of tourist services of the Hotel El Auca. With the establishment of strategies, we proceeded to define the respective strategic objectives for each one, and with this in the Discussion section of the present work, we proceeded to the formulation or proposal of the Strategic Marketing Plan for the Hotel El Auca. Once the respective strategic marketing plan was developed, it was possible to determine the total budget of $ 14,535.50 to carry out its development. Finally, the Conclusions, Recommendations with short guidelines to be followed by the Hotel El Auca are established.